Teachers and Students Needs Analysis for the Development of Subject Specific Pedagogy (SSP) Blended Learning Based on Multiple Representations - Sri Mulyani; Elfi Susanti VH; Nurma Yunita Indriyanti; Rachma Kharolinasari (Postgraduate, University of Mataram, 2023)
This article discusses the needs analysis of the teachers and students towards the development of a multiple-representation-based blended learning Subject Specific Pedagogy (SSP) used in chemistry learning. The subjects of this study consisted of 15 chemistry teachers in Central Java and 34 high school students in class XII IPA. Primary data were obtained by providing teacher questionnaires consisting of the characteristics of reaction rates material, the use of learning media that are usually used, and students' critical thinking skills and learning using SSP blended learning based on multiple representations. While the student questionnaire consists of students' interests and learning methods in understanding chemical material, students' opinions regarding the reaction level material, and students' general critical thinking skills. The results of this need analysis show that teachers and students need integrated learning tools to support learning activities. The conclusion of this study is to develop a multiple-representation-based blended learning Subject Specific Pedagogy (SSP) to improve critical thinking skills and student learning outcomes